Post-war dilemmas of Sri Lanka democracy and reconciliation - Keethaponcalan, S. I. (2019)
"By investigating Sri Lanka as a case study, this book examines whether democracy, compared to authoritarianism, is conducive to post-war reconciliation"--
Keywords: Democracy -- Sri Lanka; Authoritarianism -- Sri Lanka; Reconciliation -- Political aspects -- Sri Lanka; Sri Lanka -- History -- Civil War, 1983-2009 -- Peace; Sri Lanka -- Politics and government -- 1978-